PENDAMPINGAN KEGIATAN KEBUGARAN JASMANI MELALUI SENAM IRAMA DI SDI ENDE 7 - Marieta Yurnianti Soke; Marselina Indriani Dhoni; Rosalia Meli; Alexius Resi Koten; Oktavianus Feko Deru (JURNAL PENGABDIAN MANDIRI, 2024)
Physical education, sports and health is an integral part of overall education, aiming to develop aspects of physical fitness, movement skills, critical thinking skills, social skills, reasoning, emotional stability, moral actions, aspects of a healthy lifestyle, and introduction to a clean environment through physical activity. , sports and health. Physical fitness for elementary school children is the main aspect in supporting children's growth and development, especially elementary school children. Through observations by members of the Flores University student group at SDI Ende 7, they found that the gymnastics movements carried out by the students had not been carried out optimally. The aim of the mentoring is to find out how physical education, especially gymnastics, influences students' physical fitness levels. This activity is carried out with face-to-face learning outside the classroom (field) in class 4B. Learning uses audio media and is driven directly by the teacher, so that students must pay maximum attention to the instructor when doing gymnastics movements. The result of this activity is that students can perform gymnastic movements well, so that their bodies feel fresher and fitter.